(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2017)
Promotion as a part of marketing that is known like a heart of organizational well functioning, has a crucial role in achievement of the organization’s goals – University’s goals. The purpose of this study is to identify the most important promotional and communication strategies and their impact in attracting the prospective students in higher education for the case of the Republic of Macedonia. This study provides descriptive statistics and categorizes the order of importance of the identified marketing strategies. Different promotion techniques have been considered in order to find out their impact in attracting new students. Theoretically, it looks like the need to put changes on marketing and promotion strategies in order to re-organize the market of higher education institutions, appeals as the exact case of business cycles in accordance to the market dynamics and competition. A survey using stratified random sampling was conducted, with 8 universities from different areas in Republic of Macedonia randomly selected for the study. The approach was taken a quantitative survey of first semester students registered at public and private universities. Based on the results from of the research, hear-sayings is the main technique affecting the registration of the students followed by direct marketing, university’s website, debates & forums and others techniques. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.